Pengaruh Keputusan Investasi, Likuiditas, dan Profitabilitas Terhadap Nilai Perusahaan dengan Kebijakan Deviden sebagai Variabel Intervening di Sektor Barang Konsumen Primer yang Tercatat di BEI Tahun 2017-2021 - Kurniawati, Aji; Wiyono, Gendro; Rinofah, Risal (Universitas Batanghari Jambi, 2024)
This study aims to analyze the effect of investment decisions, liquidity, and profitability on company value with dividend policy as an intervening variable in primary consumer goods companies listed on the IDX in 2017-2021. This study used quantitative methods. The samples used were a number of 25 companies with the sampling technique used was purposive sampling. Data were analyzed using multiple linear regression, t-test and f-test with SPSS 25 program and sobel test. Investment Decision Variables are calculated by Market to Book Value of Assets (MBVA), Liquidity is calculated by Current Ratio (CR), Profitability is calculated by Return On Asset (ROA), Company Value is calculated by Price Book Value (PBV), while Dividend Policy is calculated by Devidend Payout Ratio (DPR). The results showed that investment decisions have a positive and significant influence on dividend policy, liquidity has a negative and insignificant effect on dividend policy, profitability has a positive and significant effect on dividend policy, investment decisions have a positive and significant effect on company value, liquidity has a negative and significant influence on the value of the company, profitability has a positive and significant effect on the value of the company, dividend policy has a positive and insignificant effect on the value of the company, dividend policy is unable to mediate the influence between investment decisions on company value, dividend policy is unable to mediate the effect between liquidity on company value, and dividend policy is unable to mediate the effect between profitability on company value.